Italian music in the 17th century in the regions of Spiš and Šariš in the Evangelical Churches of the Augsburg Confession - Marta Hulková (Musicologica Brunensia, 2018)
In the 17th century, the regions of Spiš and Šariš (Zips, Scharosch in German, Szepes, Sáros in Hungarian), which formed part of Upper Hungary, represented an intersection of diverse European cultural influences. In the economic and cultural sphere, the population maintained intense contacts with German-speaking regions in Central Europe: besides Saxony, Saxony-Anhalt, Thuringia and Prussia, primarily with Silesia and Transylvania. In the field of religion, they joined Luther's Reformation of the Augsburg Confession. From German printing houses, not only German Baroque music made its way to the region of Spiš and Šariš but also Italian music, primarily as part of the repertoire of musical anthologies. Ongoing research, which focuses not only on the compositions that were available in a printed form but also on pieces that were circulated in the form of manuscripts, brings a new look at the question of the distribution of the Italian musical repertoire in Central Europe during the 17th century. It enables us to get a more reliable picture about the ways in which contemporaneous musical repertoire was spread and, at the same time, reveals information about the migration of musicians in Central Europe.